Identification and Correlation Analysis of Individual Morphical and Economic Traits in Medium-Fiber Cotton - O. R, Ergashev; I. T, Kakhhorov; Sh. E, Abdurasulov; E.Yu., Karimov; N. N, Sanayev; S. D., Rakhmonov; G. Ch, Kholliev; A. A., Mutalov; F. Sh., Abdurasulov (American Journal of Biology and Natural Sciences, 2025)
The article analyzes the results of research conducted in an experimental plot established in 2021 in the Tashkent region of the Republic of Uzbekistan to identify the manifestation of individual morpho-economic traits in Gossypium hirsutum L. varieties and lines, as well as to establish correlation relationships between them. It was established that the highest stem height was observed in the AN-Boyaut-2 variety, and the lowest in the Kelajak variety. The highest number of fruiting branches was noted in the Mehnat variety, while the T-1326 line showed minimal indicators for this trait. The mass of raw cotton in one boll was highest in the T-1391 and T-1278 lines, and lowest in the T-1470 line and the standard Namangan-77 variety. The total number of bolls was highest in the T-826 and UzFA-710 forms, and lowest in the T-8588 and T-1777 lines. At the beginning of September, the highest number of opened bolls was observed in the Yulduz, T-840, UzFA-710, and Kelajak genotypes, while the Namangan-77 variety showed minimal boll opening. Five-lobed bolls dominated in the AN-Boyovut-2, T-8588, Yulduz, and Kelajak genotypes, while four-lobed bolls dominated in the UzFA-707 and UzFA-710 varieties. Fiber length was high in the T-1470 line and UzFA-707, S-6524, UzFA-710, and Kelajak varieties, while this indicator was minimal in the AN-Boyovut-2, Namangan-77 varieties, and the T-8588 line. The fiber yield was highest in the UzFA-710, Mehnat, UzFA-707, Yulduz, T-19, and T-1391 genotypes, while it was lower in the AN-Boyovut-2 variety and the T-1470 line. It was established that there are both weak positive and negative correlations between individual traits in populations, while a reliable average positive correlation was recorded between the total number and the number of opened bolls.